Phase shift mask blank, phase shift mask, and method of manufacturing phase shift mask

By introducing a phase difference adjustment layer, a gradient layer and an anti-aircraft layer into the lithography mask sheet, the problems of uneven surface atomization and stress relaxation of the photolithography mask sheet in the prior art are solved, and high-quality lithography mask sheet production is achieved.

JP7648412B2Active Publication Date: 2025-03-18TEKSCEND PHOTOMASK CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021045517
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-19
Publication Date
2025-03-18
Estimated Expiration
2041-03-19

AI Technical Summary

Technical Problem

The prior art is difficult to effectively suppress the atomization phenomenon of lithography mask sheet surface, and in a multi-layer structure, uneven stress relaxation leads to a decrease in contact force, affecting the transfer performance.

Method used

A photolithographic mask sheet structure is adopted that includes a phase difference adjustment layer, a gradient layer and an anti-aircraft layer. The phase difference adjustment layer optimizes the lithographic performance by adjusting the phase difference and mittance, the gradient layer reduces stress differences and contact force reduction by gradually changing the material composition, and the anti-aircraft layer suppresses atomization by preventing the entry of oxidative gas.

Benefits of technology

The surface atomization phenomenon of the lithographic mask sheet is effectively suppressed, the cleaning resistance and transfer performance of the mask sheet are improved, and the high-quality output of the lithographic mask sheet is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648412000002
    Figure 0007648412000002
  • Figure 0007648412000003
    Figure 0007648412000003
  • Figure 0007648412000004
    Figure 0007648412000004
Patent Text Reader

Abstract

To provide a phase shift mask blank improved in transfer performance by suppressing generation of haze on a phase shift film surface and by reducing a step in film peeling during cleaning or a corrected portion cross-section generated during correction etching, a phase shift mask and a manufacturing method of the phase shift mask.SOLUTION: A phase shift mask blank 10 according to the present embodiment is a phase shift mask blank used for manufacturing a phase shift mask to which exposure light with a wavelength of 200 nm or less is applied, and comprises a transparent substrate 11 and a phase shift film 12 formed on the transparent substrate 11, the phase shift film 12 includes a phase difference transmittance adjusting layer 13, a gas permeation protective layer 15, and a composition gradient layer 14, and in the composition gradient layer 14, a content of a component constituting the phase difference transmittance adjusting layer 13 reduces from the substrate 11 side toward a gas transmission protective layer 15 side, and a content of a component constituting the gas transmission protective layer 15 increases from the substrate 11 side toward the gas transmission protective layer 15 side.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a phase shift mask blank, a phase shift mask, and a method for manufacturing a phase shift mask, which are used in the manufacture of semiconductor devices and the like. [Background technology]

[0002] In recent years, in semiconductor processing, particularly with the increasing integration of large-scale integrated circuits, finer circuit patterns have become necessary, and there is an increasing demand for finer technology for the wiring patterns and contact hole patterns that make up the circuits. As a result, the exposure light source used in the manufacture of semiconductor devices, etc. is becoming shorter in wavelength, from KrF excimer lasers (wavelength 248 nm) to ArF excimer lasers (wavelength 193 nm).

[0003] Furthermore, as a mask with improved wafer transfer characteristics, there is, for example, a phase shift mask. In a phase shift mask, it is possible to adjust both the phase difference and the transmittance, such that the phase difference (hereinafter simply referred to as "phase difference") between the ArF excimer laser light transmitted through the transparent substrate and the ArF excimer laser light transmitted through both the transparent substrate and the phase shift film is 180 degrees, and the ratio (hereinafter simply referred to as "transmittance") of the amount of ArF excimer laser light transmitted through both the transparent substrate and the phase shift film to the amount of ArF excimer laser light transmitted through the transparent substrate is 6%.

[0004] For example, when manufacturing a phase shift mask with a phase difference of 180 degrees, a known method is to set the thickness of the phase shift film so that the phase difference is around 177 degrees, and then dry etch the phase shift film with a fluorine-based gas while simultaneously processing the transparent substrate by about 3 nm, thereby finally adjusting the phase difference to around 180 degrees. In phase shift masks that use exposure light with a wavelength of 200 nm or less, foreign matter called "haze" gradually forms, grows, and becomes evident on the mask as a result of exposure, which can make the mask unusable. In particular, when the phase shift film is made of silicon, transition metals, and light elements such as oxygen and nitrogen, foreign matter can form on the surface of the phase shift film.

[0005] Techniques for suppressing haze are described in, for example, Patent Documents 1 and 2. However, the techniques described in Patent Documents 1 and 2 may not be effective enough in suppressing the above-mentioned haze. In a method for manufacturing a phase shift mask blank using exposure light with a wavelength of 200 nm or less, a phase shift film is usually formed on a substrate by sputtering. The formed phase shift film has stress, and the film stress is partially released by etching during the phase shift mask manufacturing process, which may result in a deterioration in the positional accuracy of the phase shift mask pattern.

[0006] As a technique for relieving the stress of a phase shift film, for example, there is one described in Patent Document 3. However, in the technology described in Patent Document 3, especially when the phase shift film is a multi-layer structure made of films with different compositions, the degree of stress relaxation differs for each film constituting the phase shift film, so that the adhesion strength at the film interface decreases, and the film may peel off when the phase shift mask is washed. In other words, one method for suppressing the generation of haze on the phase shift mask is to stack the phase shift films, that is, to form a multi-layer phase shift film, but in this case, the interlayer adhesion strength in the phase shift film decreases, and the film may peel off when the phase shift mask is washed. As a result, the transfer performance may be deteriorated.

[0007] Furthermore, when the phase shift film has a multilayer structure formed of films of different compositions, the correction etching rate during mask pattern correction differs for each film, which may result in a step in the cross-sectional shape of the corrected area, resulting in deterioration of transfer performance. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2018-173621 A [Patent Document 2] Patent No. 4579728 [Patent Document 3] Patent No. 4687929 Summary of the Invention [Problem to be solved by the invention]

[0009] The present invention has been made under the above circumstances, and aims to provide a phase shift mask blank capable of sufficiently suppressing the generation of haze on the surface of a phase shift film, a phase shift mask with few haze defects and good pattern cleaning resistance and transfer performance, and a method for manufacturing the phase shift mask. That is, the present invention aims to provide a phase shift mask blank, a phase shift mask, and a method for manufacturing a phase shift mask, which suppress the generation of haze on the surface of the phase shift film and improve the transfer performance by reducing film peeling during cleaning and steps at the cross section of the repaired part generated during repair etching. [Means for solving the problem]

[0010] The present invention has been made to solve the above-mentioned problems. A phase shift mask blank according to one embodiment of the present invention is a phase shift mask blank used for producing a phase shift mask to which exposure light having a wavelength of 200 nm or less is applied, comprising a transparent substrate and a phase shift film formed on the transparent substrate, the phase shift film comprising: a phase difference transmittance adjusting layer capable of adjusting a predetermined amount of phase and transmittance for the transmitted exposure light, a gas permeable protective layer formed on the phase difference transmittance adjusting layer and preventing gas from permeating into the phase difference transmittance adjusting layer, and a composition gradient layer located between the phase difference transmittance adjusting layer and the gas permeable protective layer, the composition gradient layer being a region in which the ratio of the content of the components constituting the phase difference transmittance adjusting layer to the content of the components constituting the gas permeable protective layer changes continuously in the film thickness direction, the composition gradient layer being characterized in that the content of the components constituting the phase difference transmittance adjusting layer decreases from the substrate side toward the gas permeable protective layer side, and the content of the components constituting the gas permeable protective layer increases from the substrate side toward the gas permeable protective layer side.

[0011] A phase shift mask according to one embodiment of the present invention is a phase shift mask having a circuit pattern and is applied with exposure light having a wavelength of 200 nm or less, the phase shift mask comprising: a transparent substrate; and a phase shift film formed on the transparent substrate. The phase shift film comprises a phase difference transmittance adjusting layer capable of adjusting a predetermined amount of phase and transmittance for the transmitted exposure light, a gas permeable protective layer formed on the phase difference transmittance adjusting layer and preventing gas from passing through the phase difference transmittance adjusting layer, and a composition gradient layer located between the phase difference transmittance adjusting layer and the gas permeable protective layer, the composition gradient layer being a region in which the ratio of the content of the components constituting the phase difference transmittance adjusting layer to the content of the components constituting the gas permeable protective layer changes continuously in the film thickness direction. The composition gradient layer is characterized in that the content of the components constituting the phase difference transmittance adjusting layer decreases from the substrate side toward the gas permeable protective layer side, and the content of the components constituting the gas permeable protective layer increases from the substrate side toward the gas permeable protective layer side.

[0012] Furthermore, a method for manufacturing a phase shift mask according to one embodiment of the present invention is a method for manufacturing a phase shift mask using the above-mentioned phase shift mask blank, and is characterized in that it includes the steps of forming a light-shielding film on the phase shift film, forming a resist pattern on the light-shielding film, forming a pattern on the light-shielding film by oxygen-containing chlorine-based etching (Cl / O-based) after forming the resist pattern, forming a pattern on the light-shielding film by fluorine-based etching (F-based) after forming the pattern on the light-shielding film, removing the resist pattern after forming the pattern on the phase shift film, and removing the light-shielding film from above the phase shift film by oxygen-containing chlorine-based etching (Cl / O-based) after removing the resist pattern. Effect of the Invention

[0013] By using the phase shift mask blank according to one embodiment of the present invention, the generation of haze on the phase shift mask can be sufficiently suppressed, and the cleaning resistance and transfer performance of the pattern can be improved. In other words, the phase shift mask blank and phase shift mask according to one embodiment of the present invention can suppress the generation of haze on the surface of the phase shift film, and can impart excellent cleaning resistance and excellent transfer performance to the phase shift mask. [Brief description of the drawings]

[0014] [Figure 1] 1 is a schematic cross-sectional view showing a configuration of a phase shift mask blank according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a diagram showing the aspect of the composition gradient of a composition gradient layer in a phase shift mask blank according to an embodiment of the present invention. [Diagram 3] 1 is a schematic cross-sectional view showing a configuration of a phase shift mask according to an embodiment of the present invention. [Figure 4] 1A to 1C are schematic cross-sectional views showing a manufacturing process of a phase shift mask using a phase shift mask blank according to an embodiment of the present invention. [Diagram 5]3 is a schematic diagram showing one side of a cross section of a phase shift film pattern after repairing a phase shift mask according to an embodiment of the present invention; FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The inventors of the present application considered that the occurrence of haze in a mask blank or mask can be reduced if all three elements, namely, the constituent material of a phase adjustment film (a phase difference transmittance adjusting layer described later) constituting a phase shift mask blank or a phase shift mask, an oxidizing gas such as water or oxygen, and exposure energy, are present, and therefore the phase shift mask blank or phase shift mask is configured as follows. That is, the phase shift mask blank, phase shift mask, and manufacturing method thereof according to this embodiment are based on the technical idea of ​​providing a gas protection layer (a so-called gas barrier layer) on the phase adjustment film to prevent the oxidizing gas from coming into contact with the constituent material of the phase adjustment film, thereby reducing the occurrence of haze.

[0016] Furthermore, the inventors of the present application have established a technology for preventing deterioration of transfer performance by gradually mixing the compositions of the phase adjustment film and the gas protection layer when providing a gas protection layer on the phase adjustment film, thereby eliminating the clear interface between the layers, thereby preventing interface peeling caused by the difference in internal stress between the films, and reducing the occurrence of steps in the pattern cross section caused by differences in correction etching rates. Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Note that the schematic cross-sectional views do not accurately reflect the actual dimensional ratio or the number of patterns, and the amount of engraving in the transparent substrate and the amount of damage to the film are omitted. Suitable embodiments of the phase shift mask blank of the present invention include the following.

[0017] (Overall structure of phase shift mask blank) Fig. 1 is a schematic cross-sectional view showing the configuration of a phase shift mask blank according to an embodiment of the present invention. A phase shift mask blank 10 shown in Fig. 1 is a phase shift mask blank used for fabricating a phase shift mask to which exposure light having a wavelength of 200 nm or less is applied, and includes a substrate (hereinafter also simply referred to as "substrate") 11 that is transparent to the exposure wavelength, and a phase shift film 12 formed on the substrate 11. The phase shift film 12 includes at least a phase difference transmittance adjusting layer (hereinafter, simply referred to as a "phase layer") 13 that can adjust a predetermined amount of phase and transmittance for the transmitted exposure light, a gas permeable protective layer (hereinafter, simply referred to as a "protective layer") 15 that is formed on the phase difference transmittance adjusting layer 13 and prevents gas from permeating into the phase difference transmittance adjusting layer 13, and a composition gradient layer (hereinafter, simply referred to as a "gradient layer") 14 that is located between the phase layer 13 and the protective layer 15 and is a section (region) in which the ratio of the composition of the phase layer 13 (the content of the components constituting the phase layer 13) to the composition of the protective layer 15 (the content of the components constituting the protective layer 15) changes continuously in the depth direction (thickness direction) of the film. In the phase shift film 12, the phase layer 13 is located on the substrate 11 side. Furthermore, when the thickness of the phase layer 13 is d1, the thickness of the gradient layer 14 is d2, and the thickness of the protective layer 15 is d3, the total thickness of d1 and d2 is greater than d3, and d3 is preferably 15 nm or less. Each layer constituting the phase shift mask blank 10 according to the embodiment of the present invention will now be described in detail.

[0018] (substrate) There is no particular limitation on the substrate 11, and as the substrate 11, for example, quartz glass, CaF2, aluminosilicate glass, or the like is generally used.

[0019] (Phase shift film) The phase shift film 12 includes a phase layer 13, a gradient layer 14, and a protective layer 15 in this order, and is formed on the substrate 11 with or without other films interposed therebetween. The phase shift film 12 is, for example, a film that is resistant to oxygen-containing chlorine-based etching (Cl / O-based) and can be etched with fluorine-based etching (F-based).

[0020] The transmittance value of the phase shift film 12 is, for example, within a range of 3% to 80% relative to the transmittance of the substrate 11, and an optimal transmittance can be appropriately selected according to a desired wafer pattern. The phase difference value of the phase shift film 12 is, for example, within a range of 160 degrees to 220 degrees, and more preferably within a range of 175 degrees to 190 degrees. That is, the phase shift film 12 may have a transmittance to the exposure light within a range of 3% to 80% and a phase difference within a range of 160 degrees to 220 degrees. When the transmittance of the phase shift film 12 to the exposure light is less than 3%, good exposure performance may not be obtained. When the phase difference is within a range of 160 degrees to 220 degrees, the required exposure performance can be easily maintained.

[0021] <Phase layer> The phase layer 13 is formed on the substrate 11 with or without other films, and is a layer that can adjust the phase and transmittance of the transmitted exposure light by a predetermined amount. Here, "adjusting the phase" means, for example, inverting the phase. Also, "transmittance" means the transmittance of the exposure light. The phase layer 13 is, for example, a single layer film containing silicon and at least one selected from transition metals, nitrogen, oxygen, and carbon, or a multilayer film or gradient film thereof, and the transmittance and phase difference for the exposure wavelength are adjusted by appropriately selecting the composition and film thickness. Here, the "gradient film" refers to a film in which the composition ratio of the components constituting the phase layer 13 is not uniform throughout the phase layer 13, but changes at a constant rate.

[0022] The phase layer 13 preferably contains silicon in the range of 20 atomic % to 60 atomic % in the element ratio of the entire phase layer 13, preferably contains transition metals in the range of 0 atomic % to 20 atomic % in the element ratio of the entire phase layer 13, preferably contains nitrogen in the range of 30 atomic % to 80 atomic % in the element ratio of the entire phase layer 13, preferably contains oxygen in the range of 0 atomic % to 30 atomic % in the element ratio of the entire phase layer 13, and preferably contains carbon in the range of 0 atomic % to 10 atomic % in the element ratio of the entire phase layer 13. The more preferable content ranges of each element in the phase layer 13 are: silicon in the range of 30 atomic % to 50 atomic % in the element ratio of the entire phase layer 13, transition metals in the range of 0 atomic % to 10 atomic % in the element ratio of the entire phase layer 13, nitrogen in the range of 40 atomic % to 70 atomic % in the element ratio of the entire phase layer 13, oxygen in the range of 0 atomic % to 20 atomic % in the element ratio of the entire phase layer 13, and carbon in the range of 0 atomic % to 5 atomic % in the element ratio of the entire phase layer 13. If the content of each element in the phase layer 13 is within the above numerical range, the phase difference as well as the transmittance of the phase layer 13 can be easily controlled.

[0023] The phase layer 13 may contain at least one of oxide, carbide, and nitride of a metal silicide. In this case, the metal constituting the metal silicide may be a transition metal, which will be described later. The transition metal contained in the phase layer 13 is preferably at least one selected from molybdenum, titanium, vanadium, cobalt, nickel, zirconium, niobium, and hafnium, and more preferably molybdenum. If the transition metal contained in the phase layer 13 is at least one selected from molybdenum, titanium, vanadium, cobalt, nickel, zirconium, niobium, and hafnium, the processing of the phase layer 13 becomes easy, and if it is molybdenum, the processing of the phase layer 13 such as etching becomes even more excellent.

[0024] When the thickness of the phase layer 13 is d1, the thickness of the gradient layer 14 is d2, and the thickness of the protective layer 15 is d3, the total thickness of the thickness d1 of the phase layer 13 and the thickness d2 of the gradient layer 14 is thicker than the thickness d3 of the protective layer 15, and the thickness d3 of the protective layer 15 may be 15 nm or less. When the thickness d3 of the protective layer 15 is made thicker than 15 nm, the optical characteristics and correction characteristics may be affected.

[0025] In this embodiment, the "phase layer 13" is a layer that is composed only of the components (compounds) that constitute the phase layer 13, and does not include the components (compounds) that constitute the protective layer 15. The "protective layer 15" is a layer that is composed only of the components (compounds) that constitute the protective layer 15, and does not include the components (compounds) that constitute the phase layer 13. The "gradient layer 14" is a layer that contains both the components (compounds) that constitute the phase layer 13 and the components (compounds) that constitute the protective layer 15. That is, the "film thickness d1 of the phase layer 13" means the thickness (film thickness) of the region that is composed only of the components that constitute the phase layer 13. The "film thickness d3 of the protective layer 15" means the thickness (film thickness) of the region that is composed only of the components that constitute the protective layer 15. The "film thickness d2 of the gradient layer 14" means the thickness (film thickness) of the region that is composed of both the components that constitute the phase layer 13 and the components that constitute the protective layer 15.

[0026] In addition, the sum of the thickness d1 of the phase layer 13 and the thickness d2 of the gradient layer 14 may be greater than 15 nm. When the sum of the thickness d1 of the phase layer 13 and the thickness d2 of the gradient layer 14 is greater than 15 nm, it becomes easy to adjust the phase and transmittance. In addition, the total thickness of the thickness d1 of the phase layer 13, the thickness d2 of the gradient layer 14, and the thickness d3 of the protective layer 15 is preferably 50 nm or more, and more preferably 70 nm or more. If the total thickness of the thickness d1 of the phase layer 13, the thickness d2 of the gradient layer 14, and the thickness d3 of the protective layer 15 is within the above numerical range, the function of the phase shift film 12 can be easily set to a desired value. Note that the thickness d1 of the phase layer 13 may be 0 nm if the transmittance and phase difference for the exposure wavelength can be sufficiently adjusted by the gradient layer 14.

[0027] <Protective layer> The protective layer 15 is formed on the gradient layer 14 without any other film therebetween, and is a layer for preventing or suppressing gas permeation (particularly, permeation of oxidizing gases such as water and oxygen) into the gradient layer 14 and the phase layer 13, i.e., a gas barrier layer. This embodiment can prevent or suppress the intrusion of gas, which is considered to be one of the factors that cause haze, into the gradient layer 14 and the phase layer 13, and therefore, when the mask is used for a long period of time (for example, when the dose on the mask is 100 kJ / cm 2 Even if the exposure temperature exceeds 100° C., the generation of haze on the surface of the phase shift mask can be prevented or suppressed. The gas (atmospheric gas) whose permeation is prevented or suppressed by the protective layer 15 is an oxidizing gas, specifically, oxygen-containing molecules, and more specifically, water molecules.

[0028] The protective layer 15 is preferably a layer that is resistant to oxygen-containing chlorine-based (Cl / O-based) gas etching, can be etched with a fluorine-based gas (F-based), and can be repaired by an EB (electron beam) repair method. The protective layer 15 is preferably a single layer film made of one or more compounds selected from tantalum metal, tantalum compounds, tungsten metal, tungsten compounds, tellurium metal, tellurium compounds, silicon metal, and silicon compounds, or a mixed film or multi-layer film of these compounds, but the composition is not particularly limited as long as it is a layer having a barrier function. Note that the above-mentioned tantalum metal, tungsten metal, tellurium metal, and silicon metal refer to the simple substance of each metal.

[0029] The protective layer 15 made of a tantalum compound is a single layer film containing tantalum and one or more elements selected from oxygen, nitrogen, and carbon, or a multilayer film or gradient film thereof. The protective layer 15 made of a tantalum compound preferably contains tantalum in the range of 10 atomic % to 90 atomic % in the entire element ratio of the protective layer 15, preferably contains oxygen in the range of 0 atomic % to 90 atomic % in the entire element ratio of the protective layer 15, preferably contains nitrogen in the range of 0 atomic % to 70 atomic % in the entire element ratio of the protective layer 15, and preferably contains carbon in the range of 0 atomic % to 20 atomic % in the entire element ratio of the protective layer 15. More preferable content ranges of each element in the protective layer 15 made of a tantalum compound are tantalum in the range of 20 atomic % to 80 atomic % in the entire element ratio of the protective layer 15, oxygen in the range of 0 atomic % to 80 atomic % in the entire element ratio of the protective layer 15, nitrogen in the range of 0 atomic % to 60 atomic % in the entire element ratio of the protective layer 15, and carbon in the range of 0 atomic % to 10 atomic % in the entire element ratio of the protective layer 15. If the content of each element in the protective layer 15 made of a tantalum compound is within the above numerical range, the barrier property of the protective layer 15 against gas permeation to the gradient layer 14 and the phase layer 13 is improved.

[0030] Moreover, the protective layer 15 made of a tungsten compound is a single layer film containing tungsten and one or more elements selected from oxygen, nitrogen, and carbon, or a multilayer film or gradient film thereof. The protective layer 15 made of a tungsten compound preferably contains tungsten in the range of 10 atomic % to 70 atomic % in the element ratio of the entire protective layer 15, preferably contains oxygen in the range of 30 atomic % to 90 atomic % in the element ratio of the entire protective layer 15, preferably contains nitrogen in the range of 0 atomic % to 20 atomic % in the element ratio of the entire protective layer 15, and preferably contains carbon in the range of 0 atomic % to 20 atomic % in the element ratio of the entire protective layer 15. More preferable content ranges of each element in the protective layer 15 made of a tungsten compound are tungsten in the range of 20 atomic % to 60 atomic % in the element ratio of the entire protective layer 15, oxygen in the range of 50 atomic % to 80 atomic % in the element ratio of the entire protective layer 15, nitrogen in the range of 0 atomic % to 10 atomic % in the element ratio of the entire protective layer 15, and carbon in the range of 0 atomic % to 10 atomic % in the element ratio of the entire protective layer 15. If the content of each element in the protective layer 15 made of a tungsten compound is within the above numerical range, the barrier property of the protective layer 15 against gas permeation to the gradient layer 14 and the phase layer 13 is improved.

[0031] The protective layer 15 made of a tellurium compound is a single layer film containing tellurium and one or more elements selected from oxygen, nitrogen, and carbon, or a multilayer film or gradient film thereof. The protective layer 15 made of a tellurium compound preferably contains tellurium in the range of 20 atomic % to 70 atomic % in the element ratio of the entire protective layer 15, preferably contains oxygen in the range of 30 atomic % to 90 atomic % in the element ratio of the entire protective layer 15, preferably contains nitrogen in the range of 0 atomic % to 20 atomic % in the element ratio of the entire protective layer 15, and preferably contains carbon in the range of 0 atomic % to 20 atomic % in the element ratio of the entire protective layer 15. More preferable content ranges of each element in the protective layer 15 made of a tellurium compound are 30 atomic % to 60 atomic % in the element ratio of the entire protective layer 15, tellurium in the range of 50 atomic % to 80 atomic % in the element ratio of the entire protective layer 15, oxygen in the range of 0 atomic % to 10 atomic % in the element ratio of the entire protective layer 15, and carbon in the range of 0 atomic % to 10 atomic % in the element ratio of the entire protective layer 15. If the content of each element in the protective layer 15 made of a tellurium compound is within the above numerical range, the barrier property of the protective layer 15 against gas permeation to the gradient layer 14 and the phase layer 13 is improved.

[0032] The protective layer 15 made of a silicon compound is a single layer film containing silicon and one or more elements selected from oxygen, nitrogen, and carbon, or a multilayer film or gradient film thereof. The protective layer 15 made of a silicon compound preferably contains silicon in the range of 20 atomic % to 70 atomic % in the element ratio of the entire protective layer 15, preferably contains oxygen in the range of 0 atomic % to 90 atomic % in the element ratio of the entire protective layer 15, preferably contains nitrogen in the range of 0 atomic % to 60 atomic % in the element ratio of the entire protective layer 15, and preferably contains carbon in the range of 0 atomic % to 20 atomic % in the element ratio of the entire protective layer 15. More preferable content ranges of each element in the protective layer 15 made of a silicon compound are silicon in the range of 30 atomic % to 60 atomic % in the element ratio of the entire protective layer 15, oxygen in the range of 0 atomic % to 80 atomic % in the element ratio of the entire protective layer 15, nitrogen in the range of 0 atomic % to 40 atomic % in the element ratio of the entire protective layer 15, and carbon in the range of 0 atomic % to 10 atomic % in the element ratio of the entire protective layer 15. If the content of each element in the protective layer 15 made of a silicon compound is within the above numerical range, the barrier property of the protective layer 15 against gas permeation to the gradient layer 14 and the phase layer 13 is improved.

[0033] As described above, if the protective layer 15 is a single layer film made of one or more compounds selected from tantalum metal, tantalum compounds, tungsten metal, tungsten compounds, tellurium metal, tellurium compounds, silicon metal, and silicon compounds, or a mixed film or multi-layer film of these compounds, it can effectively prevent gas permeation into the gradient layer 14 and the phase layer 13. As described above, the thickness d3 of the protective layer 15 is 15 nm or less, but even if the protective layer 15 is made up of multiple layers, the total thickness of the protective layer 15 may be 15 nm or less, and the thickness of each layer is not particularly limited. If the thickness d3 of the protective layer 15 is within the above-mentioned range, the barrier properties against gas permeation to the gradient layer 14 and the phase layer 13 can be maintained while maintaining the optical characteristics and correction characteristics.

[0034] <Gradient layer> The gradient layer 14 is formed on the phase layer 13 without any other film, and the protective layer 15 is formed on the gradient layer 14 without any other film. The gradient layer 14 is a layer that is responsible for alleviating the film stress difference and the correction etching rate difference between the phase layer 13 and the protective layer 15. In this embodiment, the adhesion between the phase layer 13 and the protective layer 15 is prevented from decreasing due to the film stress difference, and therefore the resistance to film peeling caused by cleaning, that is, interlayer peeling occurring between the phase layer 13 and the protective layer 15, is improved. In addition, the pattern cross-sectional step caused by the etching rate difference is reduced, so that the cross-sectional shape of the pattern side becomes linear, and the transfer performance of the phase shift mask is improved.

[0035] The gradient layer 14 is preferably a layer that is resistant to oxygen-containing chlorine-based (Cl / O-based) gas etching, can be etched with a fluorine-based gas (F-based), and can be repaired by an EB (electron beam) repair method. The composition of the gradient layer 14 is such that the ratio of the composition of the phase layer 13 to the composition of the protective layer 15 changes continuously in the depth direction of the film, and the composition ratio of the phase layer 13 in the gradient layer 14 decreases from the substrate 11 side toward the protective layer 15, while the composition ratio of the protective layer 15 in the gradient layer 14 increases from the substrate 11 side toward the protective layer 15.

[0036] In addition, the "composition of the phase layer 13" here refers to the composition of the compound constituting the phase layer 13, and does not refer to the individual element ratios such as oxygen and nitrogen contained in the phase layer 13. Similarly, the "composition of the protective layer 15" refers to the composition of the compound constituting the protective layer 15, and does not refer to the individual element ratios such as oxygen and nitrogen contained in the protective layer 15. In other words, the composition of the gradient layer 14 is such that the ratio of the content of the component (compound) constituting the phase layer 13 to the content of the component (compound) constituting the protective layer 15 changes continuously in the depth direction of the film. Specifically, the content ratio of the component constituting the phase layer 13 in the gradient layer 14 decreases from the substrate 11 side toward the protective layer 15 side, and the content ratio of the component constituting the protective layer 15 in the gradient layer 14 increases from the substrate 11 side toward the protective layer 15.

[0037] The aspect of the composition gradient of the gradient layer 14 will be described below with reference to the drawings. Fig. 2 is a schematic cross-sectional view showing the composition gradient, i.e., the component ratio, of the gradient layer 14 of this embodiment. The horizontal axis of Fig. 2 shows the distance from the substrate 11 side to the outermost surface of the phase shift film 12, and the vertical axis of Fig. 2 shows the composition ratio (component ratio) of the components (compounds) constituting each layer of the phase layer 13 and the protective layer 15. 2, the phase layer 13 is formed at a distance of d1 from the substrate 11 side (hereinafter, simply referred to as "film thickness"), the gradient layer 14 is formed on the phase layer 13 with a thickness of d2, and the protective layer 15 is further formed on the gradient layer 14 with a thickness of d3. At this time, the ratio (content ratio) of the components constituting the phase layer 13 in the gradient layer 14 decreases linearly toward the protective layer 15 side, and the ratio (content ratio) of the components constituting the protective layer 15 in the gradient layer 14 increases linearly toward the protective layer 15 side.

[0038] In the second embodiment (b) in FIG. 2, similarly to the first embodiment, the phase layer 13 is formed with a thickness of d1 from the substrate 11 side, the gradient layer 14 is formed with a thickness of d2 on the phase layer 13, and the protective layer 15 is formed with a thickness of d3 on the gradient layer 14. Here, unlike the first embodiment, in the second embodiment, the ratio of the components constituting the phase layer 13 in the gradient layer 14 decreases in a curved manner toward the protective layer 15 side, and the ratio of the components constituting the protective layer 15 in the gradient layer 14 increases in a curved manner toward the protective layer 15 side. In both the first embodiment and the second embodiment, the film thickness (position) at which the ratio of the components constituting the phase layer 13 and the ratio of the components constituting the protective layer 15 are reversed is arbitrary, and either the film thickness of the region where the ratio of the components constituting the phase layer 13 is high or the film thickness of the region where the ratio of the components constituting the protective layer 15 is high may be thicker.

[0039] 2 shows a case where the transmittance and phase difference for the exposure wavelength can be sufficiently adjusted only by the gradient layer 14, and the thickness of the phase layer 13 is 0 nm as an actual measurement value. Note that although the thickness of the phase layer 13 in the third embodiment is extremely thin, the phase layer 13 itself exists. 2 shows a case where the protective layer 15 is a multi-layer structure, in which a gradient layer 14 made of a component constituting the phase layer 13 and a component constituting the protective layer 15A is formed on the phase layer 13, and a protective layer 15B made of a component different from the component constituting the protective layer 15A is formed on the gradient layer 14. In this way, the protective layer 15 may have a single-layer structure made of one type of component (compound), or may have a laminated structure made of two or more types of components (compounds).

[0040] (Overall structure of phase shift mask) The configuration of a phase shift mask 100 according to an embodiment of the present invention will now be described. 3 is a schematic cross-sectional view showing the configuration of a phase shift mask according to an embodiment of the present invention. The phase shift mask 100 shown in FIG. 3 is a phase shift mask (i.e., a patterned phase shift mask) to which exposure light having a wavelength of 200 nm or less is applied and which has a circuit pattern, and includes a substrate 11 transparent to the exposure wavelength and a phase shift film 12 formed on the substrate 11. The phase shift film 12 includes at least a phase layer 13 capable of adjusting a predetermined amount of phase and transmittance for the transmitted exposure light, a protective layer 15 formed on the phase layer 13 and preventing gas from passing through the phase layer 13, and a gradient layer 14 located between the phase layer 13 and the protective layer 15, which is a section (region) in which the ratio of the composition of the phase layer 13 (the content of the components constituting the phase layer 13) to the composition of the protective layer 15 (the content of the components constituting the protective layer 15) changes continuously in the depth direction (thickness direction) of the film. In the phase shift film 12, the phase layer 13 is located on the substrate 11 side. Furthermore, when the thickness of the phase layer 13 is d1, the thickness of the gradient layer 14 is d2, and the thickness of the protective layer 15 is d3, the total thickness of d1 and d2 is greater than d3, and d3 is preferably 15 nm or less.

[0041] Phase shift mask 100 includes a phase shift film pattern 18 formed by removing a portion of phase shift film 12 to expose the surface of substrate 11 . The composition of each layer constituting the phase shift mask 100 according to an embodiment of the present invention is the same as the composition of each layer constituting the phase shift mask blank 10 according to the embodiment of the present invention described above, and therefore detailed explanations of the composition of each layer will be omitted.

[0042] (Method of manufacturing phase shift mask blank) A method for manufacturing a phase shift mask 100 using the phase shift mask blank 10 of this embodiment includes the steps of forming a light-shielding film 16 on the phase shift film 12, forming a resist pattern 17 on the light-shielding film 16 formed on the phase shift film 12, forming a pattern in the light-shielding film 16 by oxygen-containing chlorine-based etching (Cl / O-based) after forming the resist pattern 17, forming a pattern in the light-shielding film 16 by fluorine-based etching (F-based) after forming the pattern in the light-shielding film 16, removing the resist pattern 17 after forming the pattern in the phase shift film 12, and removing the light-shielding film 16 from above the phase shift film 12 by oxygen-containing chlorine-based etching (Cl / O-based) after removing the resist pattern 17. Here, the light-shielding film 16 according to the embodiment of the present invention will be described.

[0043] <Light-shielding film> The light-shielding film 16 is a layer formed on the phase shift mask blank 10 (protective layer 15) according to the embodiment of the present invention described above. The light-shielding film 16 is, for example, a single layer film made of chromium alone or a chromium compound, or a multilayer film or gradient film thereof. More specifically, the light-shielding film 16 made of a chromium compound is a single layer film containing chromium and one or more elements selected from nitrogen and oxygen, or a multilayer film or gradient film thereof.

[0044] The light-shielding film 16 made of a chromium compound preferably contains chromium in the range of 30 atomic % to 100 atomic % inclusive, oxygen in the range of 0 atomic % to 50 atomic % inclusive, nitrogen in the range of 0 atomic % to 50 atomic % inclusive, and carbon in the range of 0 atomic % to 10 atomic % inclusive, in terms of the element ratio of the entire light-shielding film 16. More preferred content ranges of each element in the light-shielding film 16 made of a chromium compound are chromium in the range of 50 atomic % to 100 atomic % inclusive, oxygen in the range of 0 atomic % to 40 atomic % inclusive, nitrogen in the range of 0 atomic % to 40 atomic % inclusive, and carbon in the range of 0 atomic % to 5 atomic % inclusive, in terms of the element ratio of the entire light-shielding film 16. If the content of each element in the light-shielding film 16 made of a chromium compound is within the above numerical range, the light-shielding property of the light-shielding film 16 is enhanced.

[0045] The thickness of the light-shielding film 16 is preferably, for example, in the range of 35 nm to 80 nm, particularly in the range of 40 nm to 75 nm. The light-shielding film 16 can be formed by a known method. A preferred method for obtaining a film with excellent uniformity most easily is a sputtering film formation method, but the present embodiment is not limited to the sputtering film formation method.

[0046] The target and the sputtering gas are selected according to the film composition. For example, a method for forming a film containing chromium can be exemplified by using a target containing chromium and performing reactive sputtering in only an inert gas such as argon gas, only a reactive gas such as oxygen, or a mixed gas of an inert gas and a reactive gas. The flow rate of the sputtering gas can be adjusted according to the film characteristics, and may be constant during film formation, or may be changed according to the desired composition when the amount of oxygen or nitrogen is to be changed in the thickness direction of the film. In addition, the voltage applied to the target, the distance between the target and the substrate, and the pressure in the film formation chamber may be adjusted.

[0047] Each step of the method for manufacturing the phase shift mask 100 according to the embodiment of the present invention will now be described in detail. FIG. 4 is a schematic cross-sectional view showing a manufacturing process of a phase shift mask 100 using the phase shift mask blank 10 shown in FIG. 1. FIG. 4(a) shows a process of forming a light-shielding film 16 on the phase shift film 12. FIG. 4(b) shows a process of applying a resist film on the light-shielding film 16, drawing, and then developing to form a resist pattern 17. FIG. 4(c) shows a process of patterning the light-shielding film 16 by oxygen-containing chlorine-based dry etching (Cl / O-based) along the resist pattern 17. FIG. 4(d) shows a process of patterning the phase shift film 12 by fluorine-based etching (F-based) along the pattern of the light-shielding film 16 to form a phase shift film pattern 18. FIG. 4(e) shows a process of peeling and removing the resist pattern 17 and then cleaning it. FIG. 4(f) shows a process of removing the light-shielding film 16 by oxygen-containing chlorine-based etching (Cl / O-based) from above the phase shift film 12 on which the phase shift film pattern 18 has been formed. In this way, the phase shift mask 100 according to this embodiment is manufactured.

[0048] The phase shift mask 100 according to the present embodiment is a phase shift mask to which exposure light having a wavelength of 200 nm or less is applied, and includes a substrate 11 and a phase shift film 12 formed on the substrate 11 with or without other films. The phase shift film 12 includes a phase layer 13 that can adjust a predetermined amount of phase and transmittance for the transmitted exposure light, a protective layer 15 formed on the phase layer 13 and preventing gas from passing through the phase layer 13, and a gradient layer 14 that is located between the phase layer 13 and the protective layer 15 and is a section (region) in which the ratio of the phase layer 13 (content of components constituting the phase layer 13) to the composition of the protective layer 15 (content of components constituting the protective layer 15) changes continuously in the depth direction (film thickness direction) of the film. In the phase shift film 12, the phase layer 13 is located on the substrate 11 side. The phase shift mask 100 includes a phase shift film pattern 18 formed by removing a part of the phase shift film 12 so that a part of the substrate 11 is exposed. When the thickness of the phase layer 13 is d1, the thickness of the gradient layer 14 is d2, and the thickness of the protective layer 15 is d3, it is preferable that the total thickness of d1 and d2 is greater than d3, and d3 is 15 nm or less.

[0049] In the step of FIG. 4(b), either a positive resist or a negative resist can be used as the material of the resist film, but it is preferable to use a chemically amplified resist for electron beam writing, which enables the formation of a highly accurate pattern. The thickness of the resist film is, for example, in the range of 50 nm to 250 nm. In particular, when producing a phase shift mask that requires the formation of a fine pattern, in order to prevent the pattern from collapsing, it is necessary to make the resist film thin so that the aspect ratio of the resist pattern 17 does not become large, and a thickness of 200 nm or less is preferable. On the other hand, the lower limit of the thickness of the resist film is determined by comprehensively considering conditions such as the etching resistance of the resist material used, and is preferably 60 nm or more. When a chemically amplified resist for electron beam writing is used as the resist film, the energy density of the electron beam during writing is 35 μC / cm 2 to 100μC / cm 2 After this drawing, a heat treatment and a development treatment are performed to obtain a resist pattern 17. In the step of FIG. 4(e), the resist pattern 17 may be removed by wet stripping using a stripping liquid, or by dry stripping using dry etching.

[0050] 4(c), the conditions of the oxygen-containing chlorine-based dry etching (Cl / O-based) for patterning the light-shielding film 16 made of chromium alone or a chromium compound may be known conditions used for removing a chromium compound film, and in addition to chlorine gas and oxygen gas, an inert gas such as nitrogen gas or helium gas may be mixed as necessary. The phase shift film 12 located under the light-shielding film 16 is resistant to the oxygen-containing chlorine-based dry etching (Cl / O-based), and therefore remains without being removed or patterned in this process.

[0051] In the step of FIG. 4(d), the conditions of fluorine-based dry etching (F-based) for patterning the phase shift film 12 may be known conditions used for dry etching of silicon-based compound films, tantalum compound films, molybdenum compound films, etc., and CF4, C2F6, or SF6 are generally used as the fluorine-based gas, and active gas such as oxygen or inert gas such as nitrogen gas or helium gas may be mixed as necessary. In the case of FIG. 4(d), the light-shielding film 16 or resist pattern 17 located on the upper layer of the phase shift film 12 is resistant to fluorine-based dry etching (F-based), so it is not removed or patterned in this step and remains. In FIG. 4(d), the substrate 11 is generally recessed by about 1 nm to 3 nm at the same time to prevent the phase shift film 12 from being removed, and to fine-tune the phase difference.

[0052] 4(f), the conditions for the oxygen-containing chlorine-based dry etching (Cl / O-based) for removing the light-shielding film 16 may be known conditions that have been used for removing chromium compound films, and in addition to chlorine gas and oxygen gas, an inert gas such as nitrogen gas or helium gas may be mixed as necessary. The phase shift film 12 and the substrate 11 located below the light-shielding film 16 are both resistant to the oxygen-containing chlorine-based dry etching (Cl / O-based), and therefore remain without being removed or patterned in this process.

[0053] [Example] The embodiments of the present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0054] Example 1 First, a phase layer consisting of silicon, molybdenum, oxygen, and nitrogen was deposited to a thickness of 63 nm on a quartz substrate using a multi-target DC sputtering device with three targets. The targets used were molybdenum and silicon, and the sputtering gases used were argon, oxygen, and nitrogen. Next, the amount of nitrogen introduced was gradually decreased while gradually decreasing the voltage applied to the silicon target and the molybdenum target, and a gradient layer was formed on the phase layer to a thickness of 8 nm while gradually increasing the voltage applied to the tantalum target. Next, the voltage application to the silicon target and the molybdenum target was stopped, and the voltage application to the tantalum target was continued while introducing argon and oxygen, to form a protective layer to a thickness of 2 nm on the gradient layer.

[0055] The phase shift film thus obtained was analyzed by ESCA, and found that up to a position 63 nm from the substrate side, the ratios of silicon atoms, molybdenum atoms, and nitrogen atoms were Si:Mo:O:N=30:5:20:45 (atomic %), and then from the phase layer side to the protective layer side, the ratios of silicon atoms, molybdenum atoms, and nitrogen atoms were continuously decreased at a thickness of 8 nm, and the ratios of tantalum atoms and oxygen atoms were continuously increased at a thickness of 8 nm, and then at a thickness of 2 nm, the ratio was Ta:O=30:70 (atomic %). That is, when the phase shift film of Example 1 was analyzed by ESCA, the composition ratio in the phase layer was Si:Mo:O:N=30:5:20:45 (atomic %). Moreover, the ratios of silicon atoms, molybdenum atoms, and nitrogen atoms in the gradient layer were continuously and linearly decreased from the phase layer side to the protective layer side. Moreover, the ratios of tantalum atoms and oxygen atoms in the gradient layer were continuously and linearly increased from the phase layer side to the protective layer side. Furthermore, the composition ratio in the protective layer was Ta:O=30:70 (atomic % ratio).

[0056] The phase shift film thus formed, which was composed of the phase layer, the gradient layer, and the protective layer, had a transmittance of 6% for the exposure light and a phase difference of 180 degrees. Next, a light-shielding film made of chromium, oxygen, and nitrogen was deposited on this protective layer with a thickness of 50 nm using a DC sputtering device. Chromium was used as the target, and argon, oxygen, and nitrogen were used as the sputtering gas. The composition of this light-shielding film was analyzed by ESCA and found to be Cr:O:N=55:35:10 (atomic percentage). Next, a negative chemically amplified electron beam resist was spin-coated on the light-shielding film to a thickness of 200 nm, and a pattern was formed with a dose of 35 μC / cm2 The resist was patterned by electron beam drawing at 800 .ANG., heat-treated at 110.degree. C. for 10 minutes, and developed by paddle development for 90 seconds to form a resist pattern.

[0057] Next, the light-shielding film was patterned using a dry etching device. Chlorine, oxygen, and helium were used as the etching gas, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. Overetching was performed to 100%. Next, a dry etching device was used to pattern the phase shift film consisting of the protective layer, the gradient layer, and the phase layer. CF4 and oxygen were used as the etching gas, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. The dry etching was stopped when the quartz substrate was dug to an average depth of 3 nm.

[0058] Next, the resist pattern was stripped and cleaned by washing with sulfuric acid and water. Next, the light-shielding film was removed using a dry etching device. Chlorine, oxygen, and helium were used as the etching gas, and the gas pressure was set to 10 mTorr, the ICP power to 500 W, and the bias power to 10 W. Overetching was performed by 200%. During this process, no damage was caused to the phase shift film and the quartz substrate located below the light-shielding film. In this manner, the phase shift mask of Example 1 was obtained.

[0059] Next, this phase shift mask pattern was corrected by EB correction. Fig. 5 is a schematic diagram showing one side of a cross section of a phase shift film pattern after EB correction. The edge of the phase shift film pattern after EB correction may have a step on the side of the phase shift film pattern due to differences in the correction etching rates of the phase layer, the inclined layer, or the protective layer. In this embodiment, as shown in Fig. 5, when the apex of the phase shift film pattern on the substrate side is the lower apex and the apex of the phase shift film pattern on the top surface side is the upper apex, the length of the upper apex receding from the lower apex to the inside of the phase shift film pattern is the "edge receding amount", and the length of the receding from the upper apex to the inside is the "step amount".

[0060] 5(a) is a schematic cross-sectional view of a phase shift mask according to Example 1 after correction. The phase shift film pattern according to Example 1 has its upper apex set back from its lower apex toward the inside of the phase shift film pattern, with an edge setback amount of 14 nm. Also, the step amount of the phase shift film pattern according to Example 1 was 0 nm. Generally, the smaller the "edge recession amount" and "step amount" are, the higher the transfer performance is. In this embodiment, if the sum (x+y) of the edge recession amount and the step amount (y) is less than 20 nm, there is no problem with the transfer performance, and the phase shift mask has extremely excellent transfer performance. On the other hand, if the sum (x+y) is 20 nm or more, there is a problem from the viewpoint of transfer performance. From the above measurement results, it was confirmed that in the phase shift mask of Example 1, the edge recession amount x is 14 nm and the step amount y is 0 nm, so that the sum (x+y) of the edge recession amount x and the step amount y is 14 nm, and thus the phase shift mask has excellent transfer performance.

[0061] Next, the dose at which haze occurred due to accelerated exposure was measured for this phase shift mask, and it was found to be 110 kJ / cm 2 It was. The "dose at which haze occurs due to accelerated exposure" means that the larger the value, the less likely haze is to occur. 2 If the dose is more than 100 kJ / cm, there is no problem in using a phase shift mask. 2 If the above is true, the phase shift mask is extremely unlikely to produce haze. From the above measurement results, in the case of the phase shift mask of Example 1, the dose is 110 kJ / cm 2 Therefore, it was confirmed that the occurrence of haze can be reduced.

[0062] Example 2 First, a phase layer consisting of silicon, molybdenum, oxygen, and nitrogen was deposited to a thickness of 66 nm on a quartz substrate using a multi-target DC sputtering device with three targets. The targets used were molybdenum and silicon, and the sputtering gases were argon, oxygen, and nitrogen. Next, the amount of nitrogen introduced was gradually decreased while gradually decreasing the voltage applied to the silicon target and the molybdenum target, and a gradient layer was formed on the phase layer to a thickness of 8 nm while gradually increasing the voltage applied to the tungsten target. Next, the voltage application to the silicon target and the molybdenum target was stopped, and the voltage application to the tungsten target was continued while introducing argon and oxygen, to form a protective layer with a thickness of 2 nm on the gradient layer.

[0063] The phase shift film thus obtained was analyzed by ESCA, and found that up to a position 66 nm from the substrate side, the ratios of silicon atoms, molybdenum atoms, and nitrogen atoms decreased continuously at a thickness of 8 nm from the phase layer side toward the protective layer side, and the ratios of tungsten atoms and oxygen atoms increased continuously at a thickness of 8 nm, and then W:O=25:75 (atomic % ratio) at a thickness of 2 nm. That is, when the phase shift film of Example 2 was analyzed by ESCA, the composition ratio in the phase layer was Si:Mo:O:N=35:5:15:45 (atomic % ratio). Moreover, the ratios of silicon atoms, molybdenum atoms, and nitrogen atoms in the gradient layer decreased continuously and linearly from the phase layer side toward the protective layer side. Moreover, the ratios of tungsten atoms and oxygen atoms in the gradient layer increased continuously and linearly from the phase layer side toward the protective layer side. Furthermore, the composition ratio in the protective layer was W:O=25:75 (atomic % ratio).

[0064] The phase shift film thus formed, which was composed of the phase layer, the gradient layer, and the protective layer, had a transmittance of 6% for the exposure light and a phase difference of 180 degrees. Next, a light-shielding film made of chromium, oxygen, and nitrogen was deposited on this protective layer with a thickness of 50 nm using a DC sputtering device. Chromium was used as the target, and argon, oxygen, and nitrogen were used as the sputtering gas. The composition of this light-shielding film was analyzed by ESCA and found to be Cr:O:N=55:35:10 (atomic percentage). Next, a negative chemically amplified electron beam resist was spin-coated on the light-shielding film to a thickness of 200 nm, and a pattern was formed with a dose of 35 μC / cm 2 The resist was patterned by electron beam drawing at 800 .ANG., heat-treated at 110.degree. C. for 10 minutes, and developed by paddle development for 90 seconds to form a resist pattern.

[0065] Next, the light-shielding film was patterned using a dry etching device. Chlorine, oxygen, and helium were used as the etching gas, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. Overetching was performed to 100%. Next, a dry etching device was used to pattern the phase shift film consisting of the protective layer, the gradient layer, and the phase layer. CF4 and oxygen were used as the etching gas, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. The dry etching was stopped when the quartz substrate was dug to an average depth of 3 nm.

[0066] Next, the resist pattern was stripped and cleaned by washing with sulfuric acid and water. Next, the light-shielding film was removed using a dry etching device. Chlorine, oxygen, and helium were used as the etching gas, and the gas pressure was set to 10 mTorr, the ICP power to 500 W, and the bias power to 10 W. Overetching was performed by 200%. During this process, no damage was caused to the phase shift film and the quartz substrate located below the light-shielding film. In this manner, the phase shift mask according to the second embodiment was obtained.

[0067] Next, this phase shift mask pattern was corrected by EB correction, and the cross-sectional shape of the phase shift film pattern was observed, revealing the edges as shown in Fig. 5(a) with an edge recession of 15 nm. Also, the step amount of the phase shift film pattern of Example 2 was 0 nm. Next, the dose at which haze occurred due to accelerated exposure was measured for this phase shift mask, and it was found to be 80 kJ / cm 2 It was.

[0068] From the above measurement results, in the case of the phase shift mask of Example 2, the dose is 80 kJ / cm 2 Therefore, it was confirmed that the occurrence of haze can be reduced. Furthermore, from the above measurement results, it was confirmed that in the phase shift mask of Example 2, the edge recession amount x was 15 nm and the step amount y was 0 nm, so that the sum (x+y) of the edge recession amount x and the step amount y was 15 nm, thereby providing excellent transfer performance.

[0069] Example 3 First, a phase layer consisting of silicon, molybdenum, oxygen, and nitrogen was deposited to a thickness of 66 nm on a quartz substrate using a multi-target DC sputtering device with three targets. The targets used were molybdenum and silicon, and the sputtering gases were argon, oxygen, and nitrogen. Next, the amount of nitrogen introduced was gradually decreased while gradually decreasing the voltage applied to the silicon target and the molybdenum target, and a gradient layer was formed on the phase layer to a thickness of 8 nm while gradually increasing the voltage applied to the tellurium target. Next, the voltage application to the silicon target and the molybdenum target was stopped, and the voltage application to the tellurium target was continued while introducing argon and oxygen, to form a protective layer with a thickness of 2 nm on the gradient layer.

[0070] The phase shift film thus obtained was analyzed by ESCA, and found that up to a position 66 nm from the substrate side, the ratios of silicon atoms, molybdenum atoms, and nitrogen atoms were Si:Mo:O:N=40:8:7:45 (atomic %), and then from the phase layer side to the protective layer side, the ratios of silicon atoms, molybdenum atoms, and nitrogen atoms were continuously decreased at a thickness of 8 nm, and the ratios of tellurium atoms and oxygen atoms were continuously increased at a thickness of 8 nm, and then at a thickness of 2 nm, the ratios were Te:O=35:65 (atomic %). That is, when the phase shift film of Example 3 was analyzed by ESCA, the composition ratio in the phase layer was Si:Mo:O:N=40:8:7:45 (atomic %). Moreover, the ratios of silicon atoms, molybdenum atoms, and nitrogen atoms in the gradient layer were continuously and linearly decreased from the phase layer side to the protective layer side. Moreover, the ratios of tellurium atoms and oxygen atoms in the gradient layer were continuously and linearly increased from the phase layer side to the protective layer side. Furthermore, the composition ratio in the protective layer was Te:O=35:65 (atomic % ratio).

[0071] The phase shift film thus formed, which was composed of the phase layer, the gradient layer, and the protective layer, had a transmittance of 6% for the exposure light and a phase difference of 180 degrees. Next, a light-shielding film made of chromium, oxygen, and nitrogen was deposited on this protective layer with a thickness of 50 nm using a DC sputtering device. Chromium was used as the target, and argon, oxygen, and nitrogen were used as the sputtering gas. The composition of this light-shielding film was analyzed by ESCA and found to be Cr:O:N=55:35:10 (atomic percentage). Next, a negative chemically amplified electron beam resist was spin-coated on the light-shielding film to a thickness of 200 nm, and a pattern was formed with a dose of 35 μC / cm 2 The resist was patterned by electron beam drawing at 800 .ANG., heat-treated at 110.degree. C. for 10 minutes, and developed by paddle development for 90 seconds to form a resist pattern.

[0072] Next, the light-shielding film was patterned using a dry etching device. Chlorine, oxygen, and helium were used as the etching gas, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. Overetching was performed to 100%. Next, a dry etching device was used to pattern the phase shift film consisting of the protective layer, the gradient layer, and the phase layer. CF4 and oxygen were used as the etching gas, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. The dry etching was stopped when the quartz substrate was dug to an average depth of 3 nm.

[0073] Next, the resist pattern was stripped and cleaned by washing with sulfuric acid and water. Next, the light-shielding film was removed using a dry etching device. Chlorine, oxygen, and helium were used as the etching gas, and the gas pressure was set to 10 mTorr, the ICP power to 500 W, and the bias power to 10 W. Overetching was performed by 200%. During this process, no damage was caused to the phase shift film and the quartz substrate located below the light-shielding film. In this manner, the phase shift mask of Example 3 was obtained.

[0074] Next, this phase shift mask pattern was corrected by EB correction, and the cross-sectional shape of the phase shift film pattern was observed, revealing the edge as shown in Fig. 5(a), with the edge recession amount being 14 nm. Also, the step amount of the phase shift film pattern of Example 3 was 0 nm. Furthermore, from the above measurement results, it was confirmed that in the phase shift mask of Example 3, the edge recession amount x was 14 nm and the step amount y was 0 nm, so that the sum (x+y) of the edge recession amount x and the step amount y was 14 nm, thereby providing excellent transfer performance. Next, the dose at which haze occurred due to accelerated exposure was measured for this phase shift mask, and it was found to be 75 kJ / cm 2 It was. From the above measurement results, in the case of the phase shift mask of Example 3, the dose is 75 kJ / cm 2 Therefore, it was confirmed that the occurrence of haze can be reduced.

[0075] Example 4 First, a phase layer consisting of silicon, molybdenum, oxygen, and nitrogen was deposited to a thickness of 63 nm on a quartz substrate using a multi-target DC sputtering device with two targets. The targets used were molybdenum and silicon, and the sputtering gases were argon, oxygen, and nitrogen. Next, the voltage applied to the molybdenum target was gradually reduced, and a gradient layer was formed on the phase layer to a thickness of 5 nm. Next, the voltage application to the molybdenum target was stopped, and a protective layer was formed on the gradient layer to a thickness of 8 nm.

[0076] The phase shift film thus obtained was analyzed by ESCA, and found that up to a position 63 nm from the substrate side, the ratio of molybdenum atoms and nitrogen atoms was Si:Mo:O:N=30:5:20:45 (atomic %), and then from the phase layer side to the protective layer side, the ratios of molybdenum atoms and nitrogen atoms each decreased continuously at a thickness of 5 nm, and the ratios of silicon atoms and oxygen atoms each increased continuously at a thickness of 5 nm, and then at a thickness of 8 nm, the ratio was Si:O:N=40:40:20 (atomic %). That is, when the phase shift film of Example 4 was analyzed by ESCA, the composition ratio in the phase layer was Si:Mo:O:N=30:5:20:45 (atomic %). Moreover, the ratios of molybdenum atoms and nitrogen atoms in the gradient layer were continuously and linearly decreased from the phase layer side to the protective layer side. Moreover, the ratios of silicon atoms and oxygen atoms in the gradient layer were continuously and linearly increased from the phase layer side to the protective layer side. Furthermore, the composition ratio in the protective layer was Si:O:N=40:40:20 (atomic percentage ratio).

[0077] The phase shift film thus formed, which was composed of the phase layer, the gradient layer, and the protective layer, had a transmittance of 7% for the exposure light and a phase difference of 180 degrees. Next, a light-shielding film made of chromium, oxygen, and nitrogen was deposited on this protective layer with a thickness of 50 nm using a DC sputtering device. Chromium was used as the target, and argon, oxygen, and nitrogen were used as the sputtering gas. The composition of this light-shielding film was analyzed by ESCA and found to be Cr:O:N=55:35:10 (atomic percentage). Next, a negative chemically amplified electron beam resist was spin-coated on the light-shielding film to a thickness of 200 nm, and a pattern was formed with a dose of 35 μC / cm 2 The resist was patterned by electron beam drawing at 800 .ANG., heat-treated at 110.degree. C. for 10 minutes, and developed by paddle development for 90 seconds to form a resist pattern.

[0078] Next, the light-shielding film was patterned using a dry etching device. Chlorine, oxygen, and helium were used as the etching gas, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. Overetching was performed to 100%. Next, a dry etching device was used to pattern the phase shift film consisting of the protective layer, the gradient layer, and the phase layer. CF4 and oxygen were used as the etching gas, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. The dry etching was stopped when the quartz substrate was dug to an average depth of 3 nm.

[0079] Next, the resist pattern was stripped and cleaned by washing with sulfuric acid and water. Next, the light-shielding film was removed using a dry etching device. Chlorine, oxygen, and helium were used as the etching gas, and the gas pressure was set to 10 mTorr, the ICP power to 500 W, and the bias power to 10 W. Overetching was performed by 200%. During this process, no damage was caused to the phase shift film and the quartz substrate located below the light-shielding film. In this manner, the phase shift mask of Example 4 was obtained. Next, this phase shift mask pattern was corrected by EB correction, and the cross-sectional shape of the phase shift film pattern was observed, revealing the edges as shown in Fig. 5(b), with the edge recession amount being 5 nm. Also, the step amount of the phase shift film pattern according to Example 4 was 5 nm.

[0080] Next, the dose at which haze occurred due to accelerated exposure was measured for this phase shift mask, and it was found to be 130 kJ / cm 2 It was. From the above measurement results, in the case of the phase shift mask of Example 4, the dose is 130 kJ / cm 2 Therefore, it was confirmed that the occurrence of haze can be reduced. Furthermore, from the above measurement results, it was confirmed that in the phase shift mask of Example 4, the edge recession amount x was 5 nm and the step amount y was 5 nm, so the sum (x+y) of the edge recession amount x and the step amount y was 10 nm, and the mask had excellent transfer performance.

[0081] Example 5 First, a phase layer consisting of silicon, molybdenum, oxygen, and nitrogen was deposited to a thickness of 61 nm on a quartz substrate using a multi-target DC sputtering device with three targets. The targets used were molybdenum and silicon, and the sputtering gases were argon, oxygen, and nitrogen. Next, the voltage applied to the silicon target and the molybdenum target was gradually reduced while the amount of nitrogen introduced was gradually reduced, and the voltage applied to the tantalum target was gradually increased while the amount of oxygen introduced was gradually increased, and a gradient layer was formed on the phase layer to a thickness of 5 nm. Next, the voltage application to the molybdenum target was stopped, and the voltage application to the silicon target and the tantalum target was continued while introducing argon, oxygen, and nitrogen, thereby forming a protective layer to a thickness of 8 nm on the gradient layer.

[0082] The phase shift film thus obtained was analyzed by ESCA, and found that up to a position 61 nm from the substrate side, the ratios of silicon atoms, molybdenum atoms, and nitrogen atoms were Si:Mo:O:N=30:5:20:45 (atomic %), and then from the phase layer side to the protective layer side, the ratios of silicon atoms, molybdenum atoms, and nitrogen atoms were continuously decreased at a thickness of 5 nm, and the ratios of tantalum atoms and oxygen atoms were continuously increased at a thickness of 5 nm, and then at a thickness of 8 nm, the ratios were Si:Ta:O:N=20:20:40:20 (atomic %). That is, when the phase shift film of Example 5 was analyzed by ESCA, the composition ratio in the phase layer was Si:Mo:O:N=30:5:20:45 (atomic %). Moreover, the ratios of silicon atoms, molybdenum atoms, and nitrogen atoms in the gradient layer were continuously and linearly decreased from the phase layer side to the protective layer side. Moreover, the ratios of tantalum atoms and oxygen atoms in the gradient layer were continuously and linearly increased from the phase layer side to the protective layer side. Furthermore, the composition ratio in the protective layer was Si:Ta:O:N=20:20:40:20 (atomic percentage ratio).

[0083] The phase shift film thus formed, which was composed of the phase layer, the gradient layer, and the protective layer, had a transmittance of 6% for the exposure light and a phase difference of 180 degrees. Next, a light-shielding film made of chromium, oxygen, and nitrogen was deposited on this protective layer with a thickness of 50 nm using a DC sputtering device. Chromium was used as the target, and argon, oxygen, and nitrogen were used as the sputtering gas. The composition of this light-shielding film was analyzed by ESCA and found to be Cr:O:N=55:35:10 (atomic percentage). Next, a negative chemically amplified electron beam resist was spin-coated on the light-shielding film to a thickness of 200 nm, and a pattern was formed with a dose of 35 μC / cm 2 The resist was patterned by electron beam drawing at 800 .ANG., heat-treated at 110.degree. C. for 10 minutes, and developed by paddle development for 90 seconds to form a resist pattern.

[0084] Next, the light-shielding film was patterned using a dry etching device. Chlorine, oxygen, and helium were used as the etching gas, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. Overetching was performed to 100%. Next, a dry etching device was used to pattern the phase shift film consisting of the protective layer, the gradient layer, and the phase layer. CF4 and oxygen were used as the etching gas, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. The dry etching was stopped when the quartz substrate was dug to an average depth of 3 nm.

[0085] Next, the resist pattern was stripped and cleaned by washing with sulfuric acid and water. Next, the light-shielding film was removed using a dry etching device. Chlorine, oxygen, and helium were used as the etching gas, and the gas pressure was set to 10 mTorr, the ICP power to 500 W, and the bias power to 10 W. Overetching was performed by 200%. During this process, no damage was caused to the phase shift film and the quartz substrate located below the light-shielding film. In this manner, the phase shift mask of Example 5 was obtained. Next, this phase shift mask pattern was corrected by EB correction, and the cross-sectional shape of the phase shift film pattern was observed, revealing the edges as shown in Fig. 5(b), with the edge recession amount being 12 nm. Also, the step amount of the phase shift film pattern of Example 5 was 5 nm.

[0086] Next, the dose at which haze occurred due to accelerated exposure was measured for this phase shift mask, and it was found to be 150 kJ / cm 2 It was. From the above measurement results, in the case of the phase shift mask of Example 5, the dose is 150 kJ / cm 2 Therefore, it was confirmed that the occurrence of haze can be reduced. In addition, from the above measurement results, it was confirmed that the phase shift mask of Example 5 has an edge recession amount x of 12 nm and a step amount y of 5 nm, and therefore the sum (x+y) of the edge recession amount x and the step amount y is 17 nm, and thus has excellent transfer performance.

[0087] Example 6 First, a phase layer consisting of silicon, molybdenum, oxygen, and nitrogen was deposited to a thickness of 63 nm on a quartz substrate using a multi-target DC sputtering device with three targets. The targets used were molybdenum and silicon, and the sputtering gases used were argon, oxygen, and nitrogen. Next, while maintaining the voltage applied to the silicon target, the voltage applied to the molybdenum target was gradually reduced while the amount of nitrogen introduced was gradually reduced, and the voltage applied to the tantalum target was gradually increased while the amount of oxygen introduced was gradually increased, thereby forming a gradient layer with a thickness of 5 nm on the phase layer. Next, the voltage application to the tantalum target was stopped, and the voltage application to the silicon target was continued while introducing argon, oxygen, and nitrogen, thereby forming a protective layer to a thickness of 8 nm on the gradient layer.

[0088] The phase shift film thus obtained was analyzed by ESCA, and found that up to a position 63 nm from the substrate side, the ratios of silicon atoms, molybdenum atoms, and nitrogen atoms were Si:Mo:O:N=30:5:20:45 (atomic %), and then from the phase layer side to the protective layer side, the ratios of silicon atoms, molybdenum atoms, and nitrogen atoms were continuously decreased at a thickness of 5 nm, and the ratios of tantalum atoms and oxygen atoms were continuously increased at a thickness of 5 nm, and then at a thickness of 8 nm, the ratios were Si:O:N=40:40:20 (atomic %). That is, when the phase shift film of Example 6 was analyzed by ESCA, the composition ratio in the phase layer was Si:Mo:O:N=30:5:20:45 (atomic %). Moreover, the ratios of silicon atoms, molybdenum atoms, and nitrogen atoms in the gradient layer were continuously and linearly decreased from the phase layer side to the protective layer side. Moreover, the ratios of tantalum atoms and oxygen atoms in the gradient layer were continuously and linearly increased from the phase layer side to the protective layer side. Furthermore, the composition ratio in the protective layer was Si:O:N = 40:40:20 (atomic %). The composition ratio of the outermost surface of the gradient layer, i.e., the composition ratio in the interface region between the gradient layer and the protective layer, was Ta:Si:O:N = 20:20:40:20 (atomic %). Here, in the table, the interface region between the gradient layer and the protective layer, which has the above composition, is indicated as "protective layer 1," and since its film thickness was extremely thin, its value was indicated as 0 nm.

[0089] The phase shift film thus formed, which was composed of the phase layer, the gradient layer, and the protective layer, had a transmittance of 6% for the exposure light and a phase difference of 180 degrees. Next, a light-shielding film made of chromium, oxygen, and nitrogen was deposited on this protective layer with a thickness of 50 nm using a DC sputtering device. Chromium was used as the target, and argon, oxygen, and nitrogen were used as the sputtering gas. The composition of this light-shielding film was analyzed by ESCA and found to be Cr:O:N=55:35:10 (atomic percentage). Next, a negative chemically amplified electron beam resist was spin-coated on the light-shielding film to a thickness of 200 nm, and a pattern was formed with a dose of 35 μC / cm 2 The resist was patterned by electron beam drawing at 800 .ANG., heat-treated at 110.degree. C. for 10 minutes, and developed by paddle development for 90 seconds to form a resist pattern.

[0090] Next, the light-shielding film was patterned using a dry etching device. Chlorine, oxygen, and helium were used as the etching gas, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. Overetching was performed to 100%. Next, a dry etching device was used to pattern the phase shift film consisting of the protective layer, the gradient layer, and the phase layer. CF4 and oxygen were used as the etching gas, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. The dry etching was stopped when the quartz substrate was dug to an average depth of 3 nm.

[0091] Next, the resist pattern was stripped and cleaned by washing with sulfuric acid and water. Next, the light-shielding film was removed using a dry etching device. Chlorine, oxygen, and helium were used as the etching gas, and the gas pressure was set to 10 mTorr, the ICP power to 500 W, and the bias power to 10 W. Overetching was performed by 200%. During this process, no damage was caused to the phase shift film and the quartz substrate located below the light-shielding film. In this manner, the phase shift mask of Example 6 was obtained. Next, this phase shift mask pattern was corrected by EB correction, and the cross-sectional shape of the phase shift film pattern was observed, revealing the edges as shown in Fig. 5(b), with the edge recession amount being 7 nm. Also, the step amount of the phase shift film pattern of Example 6 was 7 nm.

[0092] Next, the dose at which haze occurred due to accelerated exposure was measured for this phase shift mask, and it was found to be 140 kJ / cm 2 It was. From the above measurement results, in the case of the phase shift mask of Example 6, the dose is 140 kJ / cm 2 Therefore, it was confirmed that the occurrence of haze can be reduced. In addition, from the above measurement results, it was confirmed that the phase shift mask of Example 6 has an edge recession amount x of 7 nm and a step amount y of 7 nm, and therefore the sum (x+y) of the edge recession amount x and the step amount y is 14 nm, and thus has excellent transfer performance.

[0093] [Comparative Example] Comparative Example 1 First, a phase layer consisting of silicon, molybdenum, oxygen, and nitrogen was deposited to a thickness of 65 nm on a quartz substrate using a multi-target DC sputtering device with three targets. The targets used were molybdenum and silicon, and the sputtering gases were argon, oxygen, and nitrogen. Next, the voltage application to the silicon target and the molybdenum target was stopped, and the voltage application to the tantalum target was continued while introducing argon and oxygen, and a protective layer was formed on the phase layer to a thickness of 8 nm. In other words, in Comparative Example 1, a gradient layer was not formed.

[0094] The phase shift film thus obtained was analyzed by ESCA, and the composition ratio was Si:Mo:O:N=30:5:20:45 (atomic %) from the substrate side to a position 65 nm away, and then Ta:O=30:70 (atomic %) at a thickness of 8 nm. That is, the phase shift film of Comparative Example 1 was analyzed by ESCA, and the composition ratio in the phase layer was Si:Mo:O:N=30:5:20:45 (atomic %). The composition ratio in the protective layer was Ta:O=30:70 (atomic %).

[0095] The phase shift film composed of the thus formed phase layer and protective layer had a transmittance of 6% for the exposure light and a phase difference of 180 degrees. Next, a light-shielding film made of chromium, oxygen, and nitrogen was deposited on this protective layer with a thickness of 50 nm using a DC sputtering device. Chromium was used as the target, and argon, oxygen, and nitrogen were used as the sputtering gas. The composition of this light-shielding film was analyzed by ESCA and found to be Cr:O:N=55:35:10 (atomic percentage). Next, a negative chemically amplified electron beam resist was spin-coated on the light-shielding film to a thickness of 200 nm, and a pattern was formed with a dose of 35 μC / cm 2 The resist was patterned by electron beam drawing at 800 .ANG., heat-treated at 110.degree. C. for 10 minutes, and developed by paddle development for 90 seconds to form a resist pattern.

[0096] Next, the light-shielding film was patterned using a dry etching device. Chlorine, oxygen, and helium were used as the etching gas, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. Overetching was performed to 100%. Next, a dry etching device was used to pattern the phase shift film consisting of the protective layer and the phase layer. CF4 and oxygen were used as the etching gas, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. The dry etching was stopped when the quartz substrate was dug to an average depth of 3 nm.

[0097] Next, the resist pattern was stripped and cleaned by washing with sulfuric acid and water. Next, the light-shielding film was removed using a dry etching device. Chlorine, oxygen, and helium were used as the etching gas, and the gas pressure was set to 10 mTorr, the ICP power to 500 W, and the bias power to 10 W. Overetching was performed by 200%. During this process, no damage was caused to the phase shift film and the quartz substrate located below the light-shielding film. In this manner, the phase shift mask of Comparative Example 1 was obtained. Next, this phase shift mask pattern was corrected by EB correction, and the cross-sectional shape of the phase shift film pattern was observed, revealing the edges as shown in Fig. 5(a) with an edge recession of 20 nm. Also, the step amount of the phase shift film pattern in Comparative Example 1 was 0 nm.

[0098] Next, the dose at which haze occurred due to accelerated exposure was measured for this phase shift mask, and it was found to be 135 kJ / cm 2 It was. From the above measurement results, the dose of the phase shift mask of Comparative Example 1 was 135 kJ / cm 2 Therefore, it was confirmed that the occurrence of haze can be reduced. However, since the edge recession amount of the phase shift mask of Comparative Example 1 is 20 nm as described above, which is larger than the edge recession amount in each Example, it was confirmed that the transfer performance is insufficient. In other words, in the phase shift mask of Comparative Example 1, the step amount y is 0 nm, but the edge recession amount x is 20 nm, so the sum (x+y) of the edge recession amount x and the step amount y is 20 nm, and it was confirmed that the transfer performance is insufficient.

[0099] Comparative Example 2 First, a phase layer consisting of silicon, molybdenum, oxygen, and nitrogen was deposited to a thickness of 66 nm on a quartz substrate using a multi-target DC sputtering device with two targets. The targets used were molybdenum and silicon, and the sputtering gases were argon, oxygen, and nitrogen. Next, the voltage application to the molybdenum target was stopped, and the voltage application to the silicon target was continued while introducing argon, oxygen, and nitrogen, and a protective layer was formed on the phase layer to a thickness of 8 nm. In other words, in Comparative Example 2, a gradient layer was not formed.

[0100] The phase shift film thus obtained was analyzed by ESCA, and found that the composition ratio of Si:Mo:O:N was 30:5:20:45 (atomic %) from the substrate side to a position 66 nm away, and then Si:O:N was 40:40:20 (atomic %) at a thickness of 8 nm. That is, the phase shift film of Comparative Example 2 was analyzed by ESCA, and the composition ratio of the phase layer was Si:Mo:O:N was 30:5:20:45 (atomic %). The composition ratio of the protective layer was Si:O:N was 40:40:20 (atomic %).

[0101] The phase shift film composed of the thus formed phase layer and protective layer had a transmittance of 7% for the exposure light and a phase difference of 180 degrees. Next, a light-shielding film made of chromium, oxygen, and nitrogen was deposited on this protective layer with a thickness of 50 nm using a DC sputtering device. Chromium was used as the target, and argon, oxygen, and nitrogen were used as the sputtering gas. The composition of this light-shielding film was analyzed by ESCA and found to be Cr:O:N=55:35:10 (atomic percentage). Next, a negative chemically amplified electron beam resist was spin-coated on the light-shielding film to a thickness of 200 nm, and a pattern was formed with a dose of 35 μC / cm 2 The resist was patterned by electron beam drawing at 800 .ANG., heat-treated at 110.degree. C. for 10 minutes, and developed by paddle development for 90 seconds to form a resist pattern.

[0102] Next, the light-shielding film was patterned using a dry etching device. Chlorine, oxygen, and helium were used as the etching gas, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. Overetching was performed to 100%. Next, a dry etching device was used to pattern the phase shift film consisting of the protective layer and the phase layer. CF4 and oxygen were used as the etching gas, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. The dry etching was stopped when the quartz substrate was dug to an average depth of 3 nm.

[0103] Next, the resist pattern was stripped and cleaned by washing with sulfuric acid and water. Next, the light-shielding film was removed using a dry etching device. Chlorine, oxygen, and helium were used as the etching gas, and the gas pressure was set to 10 mTorr, the ICP power to 500 W, and the bias power to 10 W. Overetching was performed by 200%. During this process, no damage was caused to the phase shift film and the quartz substrate located below the light-shielding film. In this manner, a phase shift mask according to Comparative Example 2 was obtained. Next, this phase shift mask pattern was corrected by EB correction, and the cross-sectional shape of the phase shift film pattern was observed, revealing the edge as shown in Fig. 5(b) with an edge recession of 10 nm. Also, the step amount of the phase shift film pattern in Comparative Example 2 was 10 nm.

[0104] Next, the dose at which haze occurred due to accelerated exposure was measured for this phase shift mask, and it was found to be 100 kJ / cm 2 It was. From the above measurement results, the dose of the phase shift mask of Comparative Example 2 was 100 kJ / cm 2 Therefore, it was confirmed that the occurrence of haze can be reduced. However, since the step amount of the phase shift mask of Comparative Example 2 is 10 nm as described above, which is larger than the step amount in each Example, it was confirmed that the transfer performance is insufficient. In other words, since the phase shift mask of Comparative Example 2 has an edge recession amount x of 10 nm and a step amount y of 10 nm, the sum (x+y) of the edge recession amount x and the step amount y is 20 nm, and it was confirmed that the transfer performance is insufficient.

[0105] The configurations of the phase shift mask blanks and phase shift masks of Examples 1 to 6 and Comparative Examples 1 and 2 are shown in Table 1 below.

[0106] [Table 1]

[0107] From the above results, it can be seen that the phase shift masks of the respective examples can not only reduce the amount of haze generated, but also suppress the amount of edge recession and step of the pattern. Furthermore, since the amount of edge recession and step of the pattern can be suppressed, the phase shift mask can be provided with excellent transfer performance. Furthermore, in the phase shift masks of each embodiment, the phase layer and the protective layer are formed via a gradient layer, so that no clear interface is formed between the phase layer and the protective layer, thereby imparting excellent cleaning resistance to the phase shift mask.

[0108] The phase shift mask blank of the present invention and the phase shift mask produced using the same have been described above using the above examples, but the above examples are merely examples for carrying out the present invention, and the present invention is not limited to these. Furthermore, modifications of these examples are within the scope of the present invention, and it is self-evident from the above description that various other embodiments are possible within the scope of the present invention. [Industrial Applicability]

[0109] In the present invention, the composition, film thickness, and layer structure of the phase shift mask blank, as well as the manufacturing process and conditions for a phase shift mask using the same are selected within appropriate ranges, making it possible to provide a phase shift mask in which fine patterns are formed with high precision and which is suitable for the manufacture of logic devices of 28 nm or less, or memory devices of 30 nm or less. [Explanation of symbols]

[0110] 10. Phase shift mask blank 11... Substrate (substrate) transparent to the exposure wavelength 12 Phase shift film 13...Phase layer (phase difference transmittance adjustment layer) 14... Gradient layer (composition gradient layer) 15 Protective layer (gas permeable protective layer) 16. Light-shielding film 17. Resist pattern 18 Phase shift film pattern 100 Phase shift mask d1: Phase layer thickness d2: Thickness of gradient layer d3: Thickness of protective layer

Claims

1. A phase shift mask blank used for producing a phase shift mask to which exposure light having a wavelength of 200 nm or less is applied, A transparent substrate and a phase shift film formed on the transparent substrate, The phase shift film comprises a phase difference transmittance adjusting layer capable of adjusting a predetermined amount of phase and transmittance for a transmitted exposure light, a gas permeable protective layer formed on the phase difference transmittance adjusting layer and preventing gas from permeating into the phase difference transmittance adjusting layer, and a composition gradient layer located between the phase difference transmittance adjusting layer and the gas permeable protective layer, which is a region in which the ratio of the content of a component constituting the phase difference transmittance adjusting layer to the content of a component constituting the gas permeable protective layer changes continuously in the thickness direction of the film; The phase shift mask blank is characterized in that the content of the components constituting the phase difference transmittance adjusting layer decreases from the substrate side toward the gas permeable protective layer side, and the content of the components constituting the gas permeable protective layer increases from the substrate side toward the gas permeable protective layer side.

2. The retardation transmittance adjusting layer is located on the transparent substrate side, The phase shift mask blank according to claim 1, characterized in that, when the thickness of the phase difference transmittance adjusting layer is d1, the thickness of the composition gradient layer is d2, and the thickness of the gas permeable protective layer is d3, the total thickness of d1 and d2 is thicker than d3, and d3 is 15 nm or less.

3. 3. The phase shift mask blank according to claim 1, wherein the phase shift film is resistant to oxygen-containing chlorine-based etching (Cl / O-based) and can be etched with fluorine-based etching (F-based).

4. the retardation transmittance adjusting layer contains silicon and at least one selected from a transition metal, nitrogen, oxygen, and carbon; 4. The phase shift mask blank according to claim 1, wherein the transition metal is at least one selected from the group consisting of molybdenum, titanium, vanadium, cobalt, nickel, zirconium, niobium, and hafnium.

5. 5. The phase shift mask blank according to claim 1, wherein the gas permeable protective layer contains at least one selected from the group consisting of tantalum metal, tantalum compounds, tungsten metal, tungsten compounds, tellurium metal, tellurium compounds, silicon metal, and silicon compounds.

6. 6. The phase shift mask blank according to claim 5, wherein the tantalum compound contains tantalum and at least one element selected from the group consisting of oxygen, nitrogen, and carbon.

7. 6. The phase shift mask blank according to claim 5, wherein the tungsten compound contains tungsten and at least one element selected from the group consisting of oxygen, nitrogen, and carbon.

8. 6. The phase shift mask blank according to claim 5, wherein the tellurium compound contains tellurium and at least one element selected from the group consisting of oxygen, nitrogen, and carbon.

9. 6. The phase shift mask blank according to claim 5, wherein the silicon compound contains silicon and at least one element selected from the group consisting of oxygen, nitrogen, and carbon.

10. A phase shift mask having a circuit pattern and adapted to exposure light having a wavelength of 200 nm or less, A transparent substrate and a phase shift film formed on the transparent substrate, The phase shift film comprises a phase difference transmittance adjusting layer capable of adjusting a predetermined amount of phase and transmittance for a transmitted exposure light, a gas permeable protective layer formed on the phase difference transmittance adjusting layer and preventing gas from permeating into the phase difference transmittance adjusting layer, and a composition gradient layer located between the phase difference transmittance adjusting layer and the gas permeable protective layer, which is a region in which the ratio of the content of a component constituting the phase difference transmittance adjusting layer to the content of a component constituting the gas permeable protective layer changes continuously in the thickness direction of the film; The phase shift mask is characterized in that the content of the components constituting the phase difference transmittance adjusting layer decreases from the substrate side toward the gas permeable protective layer side, and the content of the components constituting the gas permeable protective layer increases from the substrate side toward the gas permeable protective layer side.

11. The retardation transmittance adjusting layer is located on the transparent substrate side, 11. The phase shift mask according to claim 10, wherein when the thickness of the phase difference transmittance adjustment layer is d1, the thickness of the composition gradient layer is d2, and the thickness of the gas permeable protective layer is d3, the total thickness of d1 and d2 is greater than d3, and d3 is 15 nm or less.

12. 12. The phase shift mask according to claim 10, wherein the phase shift film has resistance to oxygen-containing chlorine-based etching (Cl / O-based) and can be etched with fluorine-based etching (F-based).

13. the retardation transmittance adjusting layer contains silicon and at least one selected from a transition metal, nitrogen, oxygen, and carbon; 13. The phase shift mask according to claim 10, wherein the transition metal is at least one selected from the group consisting of molybdenum, titanium, vanadium, cobalt, nickel, zirconium, niobium, and hafnium.

14. 14. The phase shift mask according to claim 10, wherein the gas permeable protective layer contains at least one selected from the group consisting of tantalum metal, tantalum compounds, tungsten metal, tungsten compounds, tellurium metal, tellurium compounds, silicon metal, and silicon compounds.

15. 15. The phase shift mask according to claim 14, wherein the tantalum compound contains tantalum and at least one element selected from the group consisting of oxygen, nitrogen, and carbon.

16. 15. The phase shift mask according to claim 14, wherein the tungsten compound contains tungsten and at least one element selected from the group consisting of oxygen, nitrogen, and carbon.

17. 15. The phase shift mask according to claim 14, wherein the tellurium compound contains tellurium and at least one element selected from the group consisting of oxygen, nitrogen, and carbon.

18. 15. The phase shift mask according to claim 14, wherein the silicon compound contains silicon and at least one element selected from the group consisting of oxygen, nitrogen, and carbon.

19. A method for producing a phase shift mask using the phase shift mask blank according to any one of claims 1 to 9, comprising the steps of: forming a light-shielding film on the phase shift film; forming a resist pattern on the light-shielding film; forming a pattern on the light-shielding film by oxygen-containing chlorine-based etching (Cl / O-based) after forming the resist pattern; forming a pattern on the light-shielding film, and then forming a pattern on the phase shift film by fluorine-based etching (F-based); removing the resist pattern after forming a pattern in the phase shift film; and after removing the resist pattern, removing the light-shielding film from above the phase shift film by oxygen-containing chlorine-based etching (Cl / O-based).

Citation Information

Patent Citations

  • Phase shift mask blank, phase shift mask and manufacturing method of phase shift mask

    JP2012203317A

  • Method of manufacturing photomask blank, photomask blank, method of manufacturing photomask, photomask, and photomask metal target

    JP2018173621A

  • Mask blank and transfer mask

    JP2019185063A

  • Method for manufacturing a photomask blank, and a method for manufacturing a photomask blank and a photomask, and a photomask

    JP4579728B2

  • Method for manufacturing photomask blanks and photomasks

    JP4687929B2